The Movement of the Portuguese Modern School in today classroom. A case study - Ana Yara POSTIGO FUENTES; Pedro Francisco GONZÁLEZ ROA (Ediciones Universidad de Salamanca, 2020)
On this article we expose a current practice according to the Movement of the Portuguese Modern School. The philosophy behind the Movement and its education culture can be lived in the daily routine of this particular learning context, where the teacher organizes her work according to it. It has been carried out an ethnographic observation, an interview with the main teacher and a teacher in practice, on top of informal conversations and an analysis of the work documents in the classroom. As main results, the principles of the Movement are presented as still current and why it is relevant in the classroom.